2021
DOI: 10.1016/j.jaip.2020.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Basophil Activation Test Reduces Oral Food Challenges to Nuts and Sesame

Abstract: What is already known about this topic? The introduction of nuts and seeds in the diet of children with 1 or more nut allergies is safe and feasible; however, because of polysensitization, this often requires multiple oral food challenges (OFCs).What does this article add to our knowledge? The basophil activation test (BAT), when used after skin prick and specific IgE testing, can reduce the number of OFCs, particularly positive OFCs, maintaining very high diagnostic accuracy.How does this study impact current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 25 publications
0
46
0
1
Order By: Relevance
“…The BAT has shown to be capable to discriminate between allergic and nonallergic children, to the respective nut/seed when tested against peanut, hazelnut, cashew nut, sesame, and almond. 32 Moreover, this study reported that the use of the BAT as a second step in the diagnostic process reduced the number of OFC by 5% to 15% after equivocal SPT and IgE to extracts and components. This notion was later reinforced by further studies showing that separately the SPT and the BAT were limited in their capacity to distinguish allergy from tolerance; however, when used in conjunction as part of the diagnostic kit their ability to identify allergic and tolerant patients improved.…”
Section: The Bat and Food Allergy Diagnosismentioning
confidence: 82%
“…The BAT has shown to be capable to discriminate between allergic and nonallergic children, to the respective nut/seed when tested against peanut, hazelnut, cashew nut, sesame, and almond. 32 Moreover, this study reported that the use of the BAT as a second step in the diagnostic process reduced the number of OFC by 5% to 15% after equivocal SPT and IgE to extracts and components. This notion was later reinforced by further studies showing that separately the SPT and the BAT were limited in their capacity to distinguish allergy from tolerance; however, when used in conjunction as part of the diagnostic kit their ability to identify allergic and tolerant patients improved.…”
Section: The Bat and Food Allergy Diagnosismentioning
confidence: 82%
“…13,23 This was supported by a recent publication investigating use of both sIgE and SPT, prior to BAT for equivocal cases. 10 In our current study, however, insofar as Ses i 1 IgE is utilized for strict ruling out of SFA, the majority of patients with bona fide suspected SFA would likely need a repeat blood draw, as BAT requires fresh blood for optimal performance. 24 The clinical role of a particular allergen component may be geographical and population-specific, but the demonstrated diagnostic efficacy of Ses i 1 in Japan, 6 United States, 7 and currently in Israel makes it likely to be a globally important determinant in sesame allergy.…”
Section: Discussionmentioning
confidence: 89%
“…Research, therefore, has focused on evaluating other diagnostic indicators such as sesame skin prick test (SPT) 3 especially those containing standardized high concentrations of allergen, 4,5 serum IgE against sesame components, 6,7 and basophil reactivity to sesame. 4,[8][9][10] BAT was previously validated for use for a variety of food allergens including peanut, 11 egg, 12 tree nuts, 13 milk, 14 and sesame. 4,[8][9][10] Receiver operating characteristic (ROC) curve analysis of these tests has provided diagnostic accuracy levels of 0.77-0.86 for high-protein concentration SPT, 4,5 0.72-0.82 for Ses i 1, 6,7 and 0.86 for CD63-induced expression on basophils.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…В сомнительных случаях с диагностической целью необходимо рассмотреть проведение клеточных тестов -исследование активации базофилов [30][31][32].…”
Section: дополнительные диагностические исследованияunclassified